2004
DOI: 10.1093/annonc/mdh344
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 5-fluorouracil-based chemotherapy in elderly patients with metastatic colorectal cancer: a pooled analysis of clinical trials

Abstract: Background: Recently published population-based investigations showed elderly patients to be underrepresented in clinical trials and less often treated according to the standard therapy. Although there is evidence that elderly patients benefit from adjuvant (radio-) chemotherapy to the same extent as younger patients, no large series describes the influence of age on efficacy of chemotherapy in metastatic colorectal cancer. Patients and methods: We carried out a retrospective analysis using source data of 3825… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
1
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(113 citation statements)
references
References 44 publications
0
97
1
14
Order By: Relevance
“…This is contrary to the observations from randomised clinical trials, which showed similar efficacy and toxicity rates for 5-FU, I or O in selected older patients (X70 years) compared with younger patients (Botto, 2004;Folprecht et al, 2004;Stewart et al, 2004;Goldberg et al, 2006).…”
Section: Influence Of Age and Sex On Survivalcontrasting
confidence: 61%
See 1 more Smart Citation
“…This is contrary to the observations from randomised clinical trials, which showed similar efficacy and toxicity rates for 5-FU, I or O in selected older patients (X70 years) compared with younger patients (Botto, 2004;Folprecht et al, 2004;Stewart et al, 2004;Goldberg et al, 2006).…”
Section: Influence Of Age and Sex On Survivalcontrasting
confidence: 61%
“…Although patients aged X70 years account for 55% of newly diagnosed CRC cases in Australia ((Australian Institute of Health and Welfare (AIHW) and Australian Association of Cancer Registries (AACR), 2004)), in our cohort only 23% of patients receiving treatment were age 70 or older. However, the proportion of older patients receiving treatment with I or O off-study is greater than that typically observed in clinical trials in either adjuvant (Sargent et al, 2001) or metastatic settings (Folprecht et al, 2004). This is largely owing to the lack of appropriate trials, a higher number of comorbidities, study-imposed restrictions, and attitudes of physicians, although clinical data demonstrate that age alone is not a sufficient reason to withhold treatment (Aapro et al, 2005).…”
Section: Demographic Trendsmentioning
confidence: 97%
“…On the contrary, active elderly patients without functional impairment should be treated in the same way as younger mCRC patients (Folprecht et al, 2004). Management of the patients who are neither frail nor fit is very complex and treatment requires individualized approach.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in the Intergroup 0089 study with adjuvant 5-FU, a secondary analysis demonstrated that the elderly are as likely to tolerate chemotherapy as younger patients [8] . In the metastatic setting, a retrospective analysis of European trials showed that fit elderly patients experience similar benefit and toxicity from 5-FU [9] . A main determinant of this controversy depends on the use of different schedules: Infusional 5-FU displays a more favorable toxicity profile than bolus administration, with severe hematological toxicity seven times less frequent [7] .…”
Section: Pharmacokinetics Of Fluoropyrimidines and Oxaliplatin In Thementioning
confidence: 99%